Implementation of the Smart Parking System (SPS): A Study on Cashless Payment for Public Roadside Parking Fees in Surabaya City - Bayu Lukito Nugroho; Eko Supeno; Sulikah Asmorowati; Wundri Hapsari (Journal of Governance and Administrative Reform)
Abstract